2015
DOI: 10.1016/j.ejmhg.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution of ABO and Rh (D) blood group alleles in Silte Zone, Ethiopia

Abstract: Background: Frequency distribution of blood groups is important as it is used in modern medicine, genetic research, anthropology, and tracing ancestral relations of humans. The ABO and Rh blood groups are the most important blood groups despite the long list of several other blood groups discovered so far.Aim of the study: To study and document the frequency of ABO and Rh (D) blood groups in three ethnic groups of Silte Zone, Ethiopia.Subjects and methods: ABO and Rh (D) typing was carried out during 2012 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 11 publications
(12 reference statements)
9
44
3
3
Order By: Relevance
“…In the study from Butajira, south Ethiopia, high allelic frequency of O blood group was reported which is in an agreement with our finding. 13 In a diverse ethnic background population of Ethiopian students, blood group study also showed similarity with our result. 12 Several studies indicate O blood group is most frequent in Africa which is very common in malaria endemic regions of the world.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the study from Butajira, south Ethiopia, high allelic frequency of O blood group was reported which is in an agreement with our finding. 13 In a diverse ethnic background population of Ethiopian students, blood group study also showed similarity with our result. 12 Several studies indicate O blood group is most frequent in Africa which is very common in malaria endemic regions of the world.…”
Section: Discussionsupporting
confidence: 86%
“…18 This is because Ethiopia is a country with more than 85 different ethnic groups having their own genetic diversity with culture of intermarriages among ethnic groups. 13 Expected frequency (genotypic frequency) was calculated from allele frequencies. The Hardy-Weinberg law states that both allele and genotype frequencies will remain constant from generation to generation in an infinitely large, interbreeding population in which mating is at random and there is no selection, migration and mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since between-as well as within-country variation of ethnic groups is considerable, we cannot provide a comprehensive distribution of ABO blood groups for individuals by country or ethnic group. However, previous studies suggest that blood type B is much more prevalent in individuals of Asian and African origin than in those of European (Caucasian) origin [4,[41][42][43][44][45]. As with individuals from successor states to Yugoslavia, naturalization and reproduction may be associated with the higher frequency of blood In summary, until recently, Switzerland has predominantly received immigration from (neighboring) European countries, which share an ethnicity and similar distributions of blood groups.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the D and d alleles have p and q frequencies respectively, under HWE condition, the frequency of Rh À is equal to q 2 . The allele frequencies are now: I read the article of Tesfaye et al [5] with great interest. Based on the data presented in Tables 1 and 2 of the above mentioned article [5], the allelic frequencies (means the corrected frequencies), and deviations of the observed values from the expected values based on HWE for ABO phenotypes are presented in Table 1.…”
mentioning
confidence: 99%